2000
DOI: 10.1136/jnnp.69.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the usefulness of sural nerve biopsy

Abstract: Objective-This study aimed to determine the usefulness of sural nerve biopsy in neurological practice. Methods-The first prospective study of sural nerve biopsy in 50 consecutive patients was undertaken. The investigating neurologist declared the prebiopsy diagnosis and management plan and after 3 months an independent neurologist evaluated the contribution of the biopsy to diagnosis and management. An independent audit oYcer sought information from the patient about the adverse eVects and value of the biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 14 publications
5
59
2
1
Order By: Relevance
“…Perry and Bril reported that infections were uncommon after sural nerve biopsy and not more frequently seen among diabetic patients (12). However, infection rates of 12-14% in all types of patients have been reported (3,19), which is in accordance with our study (12%). A further aspect is the inability to work as usual after surgery, as in three of our patients, and one of them with a sick leave of 100 days.…”
Section: )supporting
confidence: 91%
See 3 more Smart Citations
“…Perry and Bril reported that infections were uncommon after sural nerve biopsy and not more frequently seen among diabetic patients (12). However, infection rates of 12-14% in all types of patients have been reported (3,19), which is in accordance with our study (12%). A further aspect is the inability to work as usual after surgery, as in three of our patients, and one of them with a sick leave of 100 days.…”
Section: )supporting
confidence: 91%
“…All our patients were meticulously informed that a second procedure was preferable as an end point in the clinical drug study, but only around one third were positive to a second biopsy, which is in accordance with our previously published data (11). This is in view of the fact that 19 out of 23 patients reported their problems at the moment as none or mild (3,4). It emphasises the need for very detailed information even to patients in clinical practice and in clinical trials, particularly considering the high "drop outs" regarding the sural nerve biopsy procedure.…”
Section: )supporting
confidence: 90%
See 2 more Smart Citations
“…Most of the articles discussed the nerve biopsy findings in specific diseases, the clinical suspicion of which had prompted the biopsy. [23][24][25][26][27][28][29][30][31][32][33][34] No article provided guidance regarding when to perform a nerve biopsy in the evaluation of DSP.…”
Section: Analysis Of Evidencementioning
confidence: 99%